Intracellular metabolism and transport of paclitaxel in ovarian cancer - Honkanen, Meija (My University, 2020)
Although traditional chemotherapies are still the backbone of ovarian cancer treatment, interpatient variability in drug response and acquired resistance still present a major hurdle. The antimitotic agent, paclitaxel, is a standard chemotherapeutic treatment of ovarian cancer. It is known to be metabolized through members of the cytochrome P450 enzyme family and transported out of the cells via ATP-binding cassette (ABC) drug efflux transporters. However, the expression of these proteins is often disrupted in cancer tissue and may greatly affect the efficacy of local response to chemotherapeutics. Since all CYP enzymes and drug transporters relevant to paclitaxel pharmacokinetics in ovarian cancer have not previously been explored, this thesis aimed to screen a battery of CYP enzymes and ABC transporters for their metabolic and transport activity of paclitaxel. Metabolic activity was screened by incubating human, recombinant CYP isoforms with paclitaxel and quantifying paclitaxel depletion at different time points by liquid chromatography-tandem mass spectrometry. Paclitaxel transport was assessed by a vesicular transport assay utilizing HEK cell-derived, inside-out membrane vesicles overexpressing efflux transporters. Additionally, the inhibitory effect of paclitaxel on efflux transporters was also assessed utilizing fluorescent substrate probes and fluorescent imaging. It was confirmed that paclitaxel is metabolized by both CYP2C8 and CYP3A4, yet no metabolic activity was observed any of the other screened CYP isoforms. Furthermore, paclitaxel was observed to be transported only via P-glycoprotein. Paclitaxel was also found to inhibit both CYP1B1 and P-glycoprotein. Finally, the data from this thesis can be utilized in establishing in silico modelling tools to translate in vitro pharmacokinetic data into clinical relevance, and eventually even aid in personalizing ovarian cancer treatment.
Keywords: paclitaxel, cytochrome P450, membrane transport proteins, ovarian neoplasms, personalised medicine